AUDIT INKLUSIF DALAM ORGANISASI PENYANDANG DISABILITAS: PELUANG DAN TANTANGAN TATA KELOLA KEUANGAN PADA LSM GARAMIN DI NUSA TENGGARA TIMUR - Windya, Yemima Eka Christi; Tkela, Melianus E.; Malingara, Berti Soli Dima; Kadji, Dedy Prasetyo; Ngaro, Graceana Januaria Christin (Jurnal Akuntansi, 2026)
This study aims to explore and evaluate the application of inclusive audit in the financial governance of LSM Garamin, a disability-focused non-governmental organization in East Nusa Tenggara. Using a qualitative conceptual–evaluative approach, this study combines document analysis and semi-structured interviews with organizational managers and beneficiary community representatives. Data were analyzed through deductive thematic analysis based on three dimensions of inclusive audit: financial compliance and governance, transparency and information accessibility, and participation and inclusion in program evaluation. The findings show that Garamin has established basic accountability practices through activity reports, financial reports, transaction records, and donor reporting documents. However, internal procedures are not yet fully documented, accessible written information for beneficiaries remains limited, and participatory evaluation has not been consistently recorded. The novelty of this study lies in developing inclusive audit as a governance framework that connects financial accountability, information accessibility, and beneficiary participation. Practically, this study provides a mapping of governance-strengthening areas that can assist disability organizations in improving financial documentation, accessible information, and participatory evaluation.